Investigation on 2D Transition Metal Chalcogenide Using Angular-Resolved Photoelectron Spectroscopy - 박수형 (The Korean Ceramic Society, 2019)
Recently, transition metal dichalcogenide (TMDC) monolayers have been the subject of research exploring the physical phenomenon generated by low dimensionality and high symmetry. One of the keys to understanding new physical observations is the electronic band structure of 2D TMDCs. Angle-resolved photoelectron spectroscopy (ARPES) is, to this point, the best technique for obtaining information on the electronic structure of 2D TMDCs. However, through ARPES research, obtaining the long-range well-ordered single crystal samples always proves a challenging and obstacle presenting issue, which has been limiting towards measuring the electronic band structures of samples. This is particularly true in general 2D TMDCs cases. Here, we introduce the approach, with a mathematical framework, to overcome such ARPES limitations by employing the high level of symmetry of 2D TMDCs. Their high symmetry enables measurement of the clear and sharp electronic band dispersion, which is dominated by the band dispersion of single-crystal TMDCs along the two high symmetry directions Γ- K and Γ-M. In addition, we present two important studies and observations for the direct measuring of the exciton binding energy and charge transfer of 2D TMDCs, both being established by the above novel approach.